Exploration and Firm Performance: The Moderating Impact of Competitive Strategy. (1st March 2017) - Su, Zhongfeng; Guo, Hai; Sun, Wei
Abstract : In this study we examine the moderating effect of competitive strategy (including differentiation and cost‐leadership strategies) on the relationship between exploration and firm performance. We find that the moderating effect of differentiation strategy is positive while that of cost‐leadership strategy is negative. And, these moderating effects are stronger in a highly competitive context. This study offers an explanation for previous mixed findings on the linkage of exploration to firm performance and enriches the discipline's knowledge regarding the performance implications of exploration. Moreover, we respond directly to the appeal in research on competitive strategy to clarify the role played by competitive strategy in profiting from exploration.